This Whispering in Our Hearts Revisited. - Reynolds, Henry (NewSouth Publishing, 2018)
How is it our minds are not satisfied? What means this whispering in the bottom of our hearts?' Listening to the whispering in his own heart, Henry Reynolds was led into the lives of remarkable and largely forgotten white humanitarians who followed their consciences and challenged the prevailing attitudes to Indigenous people. His now-classic book The Whispering in Our Hearts constructed an alternative history of Australia through the eyes of those who felt disquiet and disgust at the brutality of dispossession. These men and women fought for justice for Indigenous people even when doing so lef.